Concept and simulation of an unmanned agricultural spraying aircraft - Teles Ribeiro da Silva, João Carlos; Ismail, Kamal Abdel Radi (Revista Agrogeoambiental, 2021)
In recent years, the Brazilian agriculture production expanded by 900 % over 1990, while the cultivated areas increased at a rate of 2 % per year. Due to this expansion, pulverization turned from manual to mechanical using ground equipment and aircraft. As a result of the new tendencies, recent statistics show the negative impacts on the health of pilots and operators of terrestrial machinery and on the environment. The present study evaluates the concept of an unmanned aerial vehicle (UAV) for pulverization of defensive products, named here as AVANT. In this study, new airfoils are evaluated, lifting line technique, vortex and panels method are used to define the geometry of the wings, fuselage and tail elements. Simulations were realized to verify the performance of the AVANT during operational shots and maneuvers. The basic parameters of the proposed AVANT are, Wingspan: 6 m; Monoplane; High wing; Piston engine (gasoline); Propeller; Tractor type; Installed power: 18 hp; Length: 5.5 m; Height: 1.477 m; Tail dragger type; Tail width: 2.6 m; Empty weight: 108.585 kg; Gross weight: 150 kg; Maximum Endurance: 9 h; Fuel capacity: 28 L; Agrochemicals capacity: 20 L; The results show that the AVANT is adequate for the proposed application.